(untitled) (The International Research Journal of Management Science, 2025)
Purpose: This study investigates the long-run cointegrating relationship between personal remittances and economic growth in eight SAARC member countries, testing whether remittance inflows exert a long-run impact on real GDP per capita after controlling for foreign direct investment, population growth, and unemployment. Methods/Design: Using annual panel data from SAARC member countries (Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka) over 2000–2024, this study employed a cointegration framework to estimate long-run elasticities. Panel unit root tests (Levin-Lin-Chu) confirmed that all variables were integrated of order one [I(1)], justifying cointegration techniques. Pedroni and Kao cointegration tests provided robust evidence of a stable long-run equilibrium relationship among variables. To obtain consistent, efficient long-run parameter estimates that correct for endogeneity and serial correlation, the study employed the Fully Modified Ordinary Least Squares (FMOLS) method. Findings: The long-run FMOLS estimates revealed that remittances exert a statistically significant positive effect on real GDP per capita, and FDI also showed a positive effect. In contrast, population growth exhibited a negative and significant effect, while unemployment remained statistically insignificant. The model demonstrated strong explanatory power, with an R-squared value of 94 percent, confirming that the selected variables accounted for a substantial share of Real GDP variation. Conclusion: The findings of this study conclude that remittance inflows play an important and positive role in long-term economic growth within SAARC economies, independent of prevailing unemployment dynamics. This relationship underscores the need for macroeconomic frameworks that channel external financial flows toward capital formation rather than short-term consumption. Consequently, the evidence highlights the macro-critical role of remittances in sustaining growth paths across the region. Implications: This study contributes to the SAARC literature by presenting a novel panel cointegration analysis based on a balanced dataset extending through 2024. By estimating remittance elasticities, the findings offer valuable insights for policy formulation, particularly in managing capital inflows to enhance long-term growth outcomes.